2011
DOI: 10.1002/ijc.25762
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial cancer associated with various forms of postmenopausal hormone therapy: A case control study

Abstract: This study evaluates the effect of different modes of estradiol-progestagen therapy (EPT) regimens on the postmenopausal endometrial cancer risk in Finland. Women diagnosed with endometrial cancer in 1995-2007 at the age of 50-80 years were identified from the Finnish Cancer Registry (N 5 7,261). For each case, three age-matched controls were retrieved from the Finnish Population Register. The use of EPT since 1994 was ascertained from the national Medical Reimbursement Register. Odds ratios (ORs) for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 38 publications
(59 reference statements)
1
41
0
Order By: Relevance
“…Two prior studies demonstrated no difference in risk between cyclic therapy with norethisterone versus medroxyprogesterone. 3,22 Our study suggested a higher risk for Cancer Therapy and Prevention endometrial cancer when cyclic therapy was combined with norethisterone than if combined with levonorgestrel. Current as well as previous users of hormones had an increased risk of Type I endometrial cancer which increased with increasing duration of use.…”
Section: Discussionmentioning
confidence: 76%
“…Two prior studies demonstrated no difference in risk between cyclic therapy with norethisterone versus medroxyprogesterone. 3,22 Our study suggested a higher risk for Cancer Therapy and Prevention endometrial cancer when cyclic therapy was combined with norethisterone than if combined with levonorgestrel. Current as well as previous users of hormones had an increased risk of Type I endometrial cancer which increased with increasing duration of use.…”
Section: Discussionmentioning
confidence: 76%
“…14,15 Likewise, the most recent case control study also showed that the use of sequential and long-cycle estrogen-progestogen therapy was associated with an increased risk of endometrial cancer, whereas the use of continuous estrogen-progestogen therapy or estradiol plus LNG-IUS showed a decreased risk. 29 Another finding of this review is that the discontinuation rate tended to be lower in the ET plus LNG-IUS groups than in ET plus systemic progestogen groups.…”
Section: Summary Of Evidencementioning
confidence: 91%
“…The most common form of EC, the endometrioid (type I) variant, is generally hormonally responsive and women with an unbalanced oestrogen exposure are at increased risk for this form of EC. No risk increase was reported in women using a continuous combined HRT regimen, while the use of sequential HRT resulted in different risk profiles according to the duration of treatment (Jaakkola et al, 2011). Thus, when used for less than 5 years, the sequential E+P regimen showed a decreased risk for EC (RR 0.67, 95% CI 0.52-0.86), while continuing treatment after 5 years resulted in an increased risk for EC (RR 1.11, www.intechopen.com Several studies reported an increased risk for ovarian cancer in women using HRT (Beral et al, 2007;Morch et al, 2009), with a stronger association in the case of unopposed oestrogen administration (Hildebrand et al, 2010).…”
Section: Musculoskeletal Effectsmentioning
confidence: 90%